Educator acceptance of Education 5.0@UiTM framework and initiatives: a descriptive analysis / Mohd Idzwan Mohd Salleh ... [et al.] - Mohd Salleh, Mohd Izwan; Ibrahim, Zainuddin; Othman, Khairul Iskandar; Yusoff, Haslinda; Ariffin, Suriyani (UiTM Press, 2020)
As technology is rapidly changing our world, the way of life and a diverse array of the landscape of education, people can get education easy and it can be accessed anytime and anywhere on their own choice. Nowadays, the goal of people go to higher education is different, there is not the only the purpose of better life anymore, but it is the choice of people as students whether they want to get knowledge and skills from the university or through the experience of others or from their own experience. Some educators worry that even though education will never disappear, there will be no university anymore in the future as technology takes place a lot of the ability to teaching and learning. An Education 5.0@UiTM is a new proposed educational transformation framework and initiatives in teaching and learning pedagogy and ecosystem to face a wave of change every day and indirectly promotes many challenges. This initial study was conducted to identify the educator acceptance level of the new proposed framework and initiatives across 26 faculties and 35 campuses of Universiti Teknologi MARA Malaysia. Data was acquired through participated 370 educators in the roadshows and talks about Education 5.0@UiTM framework and initiatives.